Global Tanning Bed Advertising: A Comparison of Legal Regulations on Three Continents - Mathes, Sonja; Lindwedel, Karla; Nilsen, Lill Tove; Kaiser, Isabelle; Pfahlberg, Annette Bettina; Gefeller, Olaf (Cancers, 2023)
Artificial ultraviolet radiation from tanning beds has been classified as carcinogenic by the International Agency for Research on Cancer in 2009. Several countries have subsequently introduced comprehensive legislation regulating commercial indoor tanning. Specific aspects of these regulations address tanning bed advertising and information requirements for tanning bed customers, which have been previously neglected in international comparisons of indoor tanning regulations. We performed a systematic search regarding legislation on these aspects in 131 legislative units across three continents (North America, Australia/New Zealand, Europe). The legal restrictions found varied widely in type and content. In 49 legislative units we identified total (n = 8) or partial legal bans (n = 41) on advertising for indoor tanning, while 64 legislative units enacted 5regulations that necessitate the dissemination of different types of specific health information to tanning bed customers. Nearly 40% of the legislative units of the study region lacked any legislation on these issues altogether. The heterogenous results emphasize the need for an international dialogue between health authorities and governments to harmonize the regulatory framework for tanning bed advertising and information requirements to a level better protecting the public from skin cancer. Our comprehensive international comparison can serve as a starting point for such a harmonization process that may ultimately protect the public worldwide from misleading tanning bed advertising.
CRIS-Team Scopus Importer:2023-09-22
Keywords: advertising; legislation; sunbathing; sunbed; tanning bed; tobacco control; ultraviolet radiation

Tanning Bed Legislation for Minors: A Comprehensive International Comparison - Diehl, Katharina; Lindwedel, Karla; Mathes, Sonja; Gefeller, Olaf; Görig, Tatiana (Children, 2022)
Tanning beds have been classified as carcinogenic to humans. As a result, many countries have enacted laws regulating the use of commercial tanning beds, including bans for minors. However, there is no international overview of the current legal status of access restrictions for minors that provides details on their specific design regarding age limits and possible exceptions to the statutory regulation. Therefore, we performed a comprehensive web search of current tanning bed legislation for minors on the three continents North America, Australia, and Europe. Our findings regarding the existence and concrete design of access restrictions are presented graphically, using maps. We found a wide variety of different legislations. In Australia, a total ban on tanning beds exists, while in New Zealand, tanning bed use is banned for minors. In Europe, about half of the countries have implemented a strict ban for minors. In North America, we found differences in the age limit for access restrictions between the states, provinces, and territories for those regions that implemented a ban for minors. In the United States, some states have rather "soft bans" that allow use by minors with different types of parental consent. The patchwork in legislation calls for harmonization. Therefore, our comparison is an important starting point for institutions such as the World Health Organization or the European Commission to advance their goals toward a harmonization of tanning bed legislation in general and for minors in particular.
CRIS-Team WoS Importer:2022-07-08